Taxonomic revision of the genus Trigonosciadium (Apiaceae) in Turkey - Eroğlu Hüseyi̇n; Behçet Lütfi̇; Pinar, Süleyman Mesut (Phytotaxa, 2017)
A revision of the species of Trigonosciadium occurring in Turkey is presented. Four species are recognised, of which T. tuberosum is rediscovered in Turkey after 1887 and T. lasiocarpum is accepted as the correct name for Malabaila lasiocarpa. Furthermore, T. tuberosum subsp. undulatum is regarded as synonymous of T. viscidulum. Descriptions, anatomical and palynological features, distribution areas, threat categories according to IUCN, and an identification key are presented for all accepted species.